Implementasi Software Akuntansi pada Lembaga Amil Zakat, Infak, dan Sedekah Syamsul Ulum - Hilda Salman Said; Lestari, Tri Utami; Aminah, Wiwin (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2022)
The amil zakat institution has a public responsibility by providing reports to stakeholders. The financial reporting of the Amil Zakat Institution is regulated by the Statement of Financial Accounting Standards (PSAK) 109. However, not all of the lazis recognize and apply PSAK 109, including the Amil Zakat Infak/Alms Syamsul Ulum Institution (LAZISSU). This community service activity has been carried out in 2 stages. Phase 1 is in the form of socialization of PSAK 109 in the form of an introduction to the format of financial statements and the appropriate accounting system. Phase 2 is training and mentoring for LAZISSU amil to be able to prepare financial reports independently. The current activity is the third stage in the form of software implementation for amil zakat institutions. The method of implementing activities is direct implementation assistance. Participants are managers and Lazissu finance division team as the main users of the software. Participants combine the knowledge that has been obtained in the previous two stages into the process of implementing zakat institution software. Resource persons act as assistants in this implementation process. The result of this series of activities is that participants understand the importance of preparing financial reports for amil zakat institutions in accordance with applicable accounting standards and are able to compile financial reports with the help of accounting software that has been provided.